Doing the Charleston: My Personal History of Scholarly Communication - Strauch, Katina; Gunter, Darrell W (University of Michigan Press, 2025)
In 1980, Katina Strauch started the Charleston Conference: Issues in Book and Serial Acquisition to bring together librarians, publishers, and vendors to discuss issues shared by the three groups. The meeting has continued annually and boasts over 3,000 attendees in person and virtually. This memoir is Katina’s diary and story of the Charleston Conference and its development concurrently with her career as a professional librarian. Over the last 45 years, there have been massive changes in scholarly communication, changes that Katina has been at the heart of. Where and what will the library and publishing professions develop next? The sky’s the limit to reimagining! Let’s go.